2021
DOI: 10.1017/jfm.2021.310
|View full text |Cite
|
Sign up to set email alerts
|

Dispersive stresses in turbulent flow over riblets

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
64
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 57 publications
(207 reference statements)
6
64
0
Order By: Relevance
“…In fact, only sharp-triangular and blade riblets show a significant friction contribution of KH rollers , whereas the breakdown of the viscous regime occurs inevitably for all riblets. Furthermore, Modesti et al (2021) showed that secondary flows contribute significantly to ΔU + for various riblet shapes by analysing the dispersive stresses as a footprint of secondary flows.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, only sharp-triangular and blade riblets show a significant friction contribution of KH rollers , whereas the breakdown of the viscous regime occurs inevitably for all riblets. Furthermore, Modesti et al (2021) showed that secondary flows contribute significantly to ΔU + for various riblet shapes by analysing the dispersive stresses as a footprint of secondary flows.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Modesti et al. (2021) showed that secondary flows contribute significantly to for various riblet shapes by analysing the dispersive stresses as a footprint of secondary flows.…”
Section: Introductionmentioning
confidence: 99%
“…(2021 a , b ) and Modesti et al. (2021). Here, we extend this investigation by focusing on heat transport and its (Reynolds) analogy with momentum transport.…”
Section: Introductionmentioning
confidence: 97%
“…2020; Modesti et al. 2021), spanwise-aligned bars (Volino, Schultz & Flack 2009; Krogstad & Efros 2012) and spanwise-alternating rough-to-smooth surfaces (Bakhuis et al. 2020; Wangsawijaya et al.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst the drag behaviours of highly directional two-dimensional surfaces have been studied extensively, e.g. streamwise-aligned riblets (Gatti et al 2020;Modesti et al 2021), spanwise-aligned bars (Volino, Schultz & Flack 2009;Krogstad & Efros 2012) and spanwise-alternating rough-to-smooth surfaces (Bakhuis et al 2020;Wangsawijaya et al 2020), systematic studies of surface anisotropy in the context of irregular, three-dimensional roughness remain scarce. One exception to this trend is the work by Busse & Jelly (2020), which demonstrated that irregular roughness with spanwise-elongated features induces an over 200 % increase in U + , relative to roughness with streamwise-elongated features in fully developed turbulent channel flow.…”
Section: Introductionmentioning
confidence: 99%